Spina Bifida Occulta Is a Risk Factor for Spinal Cord Injury Without Fracture or Dislocation for Children Performing a Backbend During Dance - Liu, Guoqing; Jiang, Wei; Tang, Xiang; Tan, Shali; Zhang, Mingqiang; Tao, Liang; Xiao, Nong; Chen, Yuxia (Frontiers in Pediatrics, 2022)
Objective This study aimed to explore the clinical features and outcomes of children with spinal cord injury (SCI) without fracture or dislocation. Methods The clinical data of children with SCI without fracture or dislocation in this retrospective study were collected in Chongqing, China (January 2010 to December 2021). We collected patient demographics at admission including age, gender, cause, level, and severity of the injury in admission and complications. Reports from radiologic imaging were reviewed to identify spina bifida occulta (SBO). Neurological function was evaluated using the American Spinal Injury Association (ASIA) Impairment Scale (AIS) for an SCI. Results A total of 74 children with SCI (male, 27%; female, 73%; male-to-female ratio, 1:2.7; average age, 5.7 years) were included. The main cause of injury was backbend during the dance (34 patients, 45.9%, including 2 patients who hugged back falling backward), followed by traffic accidents (17 patients, 23%). Children with backbend-related SCI were older than other children (6.9 vs. 4.9 years old, P < 0.001). When reviewing all radiological images, it was found that 20 (27%) patients with SCI had SBO. The proportion of SCI with SBO caused by backbend was considerably higher than those caused by non-backbend (41.2 vs. 15%, P = 0.012). The AIS were 22 (29.7%), 4 (5.4%), 8 (10.8%), 31 (41.9%), and 9 (12.2%) in A, B, C, D, and E, respectively. The prognosis was poorer in the backbend during dancing than other causes of injury (p = 0.003). Conclusion This study showed that backbend during the dance was the main cause of children's SCI without fracture or dislocation in Chongqing, China. The prognosis was poorer in those children than in other causes of injury. Meanwhile, we have established an association between SBO and SCI for children performing a backbend during the dance.